Cultivating Environmental Awareness through Ayat Kauniyah-Based Ecopedagogy: A Qualitative Study in an Indonesian Islamic Junior High School - Kharisma Salma; Nurjanah (AL-ADABIYAH: Jurnal Pendidikan Agama Islam, 2026)
This study investigates how environmental awareness is cultivated through Ayat Kauniyah-Based Ecopedagogy at SMP Pembangunan Laboratorium UNP, Indonesia, and examines the challenges encountered in its implementation. The study responds to the growing ecological crisis and the need for environmental education models that integrate Islamic values with sustainable environmental practices. A qualitative case study design was employed. Data were collected through participant observation, semi-structured interviews, and document analysis involving the principal, Islamic Religious Education (PAI-BP) teachers, homeroom teachers, educational staff, and students. Data were analyzed using thematic analysis through coding, categorization, and interpretation processes, while trustworthiness was ensured through triangulation and member checking. The findings reveal that environmental awareness is cultivated through five interconnected dimensions: (1) contextual integration of ayat kauniyah into PAI-BP learning, (2) environmentally oriented school culture and daily habituation, (3) appreciation-based motivation through the Cleanest Classroom Award, (4) environmental communication through muhadharah activities, and (5) institutional support grounded in the philosophy of “Alam Takambang Jadi Guru.” These initiatives successfully transform students’ understanding of the khalifah concept into practical ecological responsibility. However, implementation remains constrained by limited instructional time, inconsistent student behavior, insufficient parental involvement, and weak cross-curricular collaboration. This study introduces the concept of Ayat Kauniyah-Based Ecopedagogy, which integrates Qur’anic ecological literacy, environmental habituation, spiritual motivation, environmental communication, and institutional reinforcement within an Islamic educational setting. The study contributes a conceptual framework for faith-based environmental education and expands the discourse on Islamic ecopedagogy by demonstrating how religious values can foster ecological awareness and pro-environmental behavior among students.